Preliminary investigation of hummocky landforms and hyper-mobility of the Bingda landslide, northeastern Tibetan Plateau - Liang, Lianji; Dai, Fuchu; Zhu, Yuxuan; Pan, Rongshen (Frontiers in Earth Science, 2025)
Rapid and long-runout landslides characterized by their high speed, long distance mobility, and huge capacity and volume would pose significant threats to infrastructure and life safety. In this study, a rapid and long-runout landslide that occurred in the Bingda village of the northeastern Tibetan Plateau, which was triggered by heavy rainfall in June 2017, was preliminarily investigated. On the basis of detailed field surveys, high-resolution satellite imagery analysis, and laboratory tests, the morphological and sedimentological features of the landslide were described, and the formation mechanism of hummocky landforms and its insight into the extraordinary movement of the Bingda landslide was deduced. The field investigation and satellite imagery analysis showed that there were nearly 200 hummocks, mostly with normal circular bases and with a height of ∼0.1 m–7.5 m, distributed in the transfer and accumulation areas of the landslide. The height and number density of the hummocks decreased away from the transfer area to the accumulation area and displayed higher heights at the outer bends of the gully channel than that at the inner bends of it. The characteristics of the spatial distribution and the composition of hummocks indicated that significant generation and dissipation of pore-water pressure within the loose and saturated silty clay layer in the runout path was the most probable reason for the formation of hummocky landforms. This study also provided insights into the hypermobility mechanisms of the Bingda landslide, suggesting that this landslide began with the sliding failure of the weathered colluvium in the source area, and then the landslide debris traveled into the channel and impacted sudden undrained loading and rapid shearing to the underlying silty clay layers in the gully. These processes generated pore-water pressure and reduced the effective stress within the soil particles, resulting in a decrease in the frictional resistance in the substrate, finally facilitating the rapid and long-runout movement of the landslide.